2017
DOI: 10.1016/j.mayocp.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Herpes Zoster: A Systematic Review and Meta-analysis

Abstract: Background. Crimean-Congo hemorrhagic fever (CCHF) is a potentially fatal disease caused by a tick-borne virus from the Bunyaviridae family. Cytokines plays an important role in the pathogenesis of viral, bacterial, and immunologic diseases. This study aimed to investigate the role of TNF-alpha, IL-6, IL-10, and IFN-gamma levels in the severity of infection and clinical outcome of patients with CCHF. Methods. Patients with confirmed CCHF were divided into two groups (severe cases: Patients who exhibited hemorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
168
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(206 citation statements)
references
References 99 publications
11
168
3
6
Order By: Relevance
“…Previously, for this same study population we found that IRs for HZ were higher in females compared with males and increased with greater age, and were highest in patients with IC conditions (and in particular those undergoing HSCT, subjects with HM and those with SLE), and somewhat lower in subjects with chronic medical conditions . Those findings are consistent with those from other epidemiological studies which report an increasing incidence of HZ with older age, and also a higher incidence in patients with malignancy, and other IC conditions such as SLE . In the further data we present here, we show that the influence of age and sex is also apparent in patients with different IC and chronic medical conditions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previously, for this same study population we found that IRs for HZ were higher in females compared with males and increased with greater age, and were highest in patients with IC conditions (and in particular those undergoing HSCT, subjects with HM and those with SLE), and somewhat lower in subjects with chronic medical conditions . Those findings are consistent with those from other epidemiological studies which report an increasing incidence of HZ with older age, and also a higher incidence in patients with malignancy, and other IC conditions such as SLE . In the further data we present here, we show that the influence of age and sex is also apparent in patients with different IC and chronic medical conditions.…”
Section: Discussionsupporting
confidence: 92%
“…The lifetime risk for developing HZ is estimated at 30% . Declining VZV‐specific cell‐mediated immunity, which predisposes an individual to VZV reactivation and clinical HZ, occurs as a result of age‐related “immunosenescence”, which may explain the greater risk and higher incidence of HZ in individuals aged 50 years or more . Incidence and risk is greater in women, in individuals with immunocompromised (IC) medical conditions (e.g., patients with hematological or solid tumors or those receiving immunosuppressive therapies) and also in individuals with certain chronic medical conditions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, patients’ age is a well‐known risk factor for HZ (Kawai & Yawn, ). Only one out of 12 patients (8·3%) without these risk factors experienced HZ following the addition of patients’ age (>56 years) to the risk factors in the present study.…”
Section: Univariate Analysis For Cumulative Incidence Of Herpes Zostermentioning
confidence: 99%
“…16,22,23 P-values were calculated using chisquare test for all the categorical variables, and Wilcoxon test for all the continuous variables. Sensitivity of diagnosis codes for HZO was examined by comparing the percentage of patients with HZO codes to the percentage of HZO patients identified by NLP.…”
Section: Application Of Nlp Algorithm and Analysismentioning
confidence: 99%